Kinematic variables of gait and quality of life in Parkinsonians after different treadmill trainings: a randomized control trial - Maira Peloggia Cursino; Doralice Fernanda Raquel; Camilla Zamfolini Hallal; Flávia Roberta Faganello Navega (Desafio Singular, 2018)
The aim of this study was to analyse and compare the effects of gait training on a treadmill associated with partial body weight support (PBWS) or auditory stimulus (AS) and the kinematic variables of gait and quality of life (QOL) in patients with Parkinson's disease (PD). Twenty-one volunteers with PD participated and were divided into: group with PBWS (GPBWS) with AS (GAS), and control group (CG). Soil step length (SL), SL variability (SLV), step width (SW), SW variability (SWV), gait speed (GS), and QOL were evaluated by the Parkinson's Disease Questionnaire-39 (PDQ-39). The training was performed for six weeks, with three weekly sessions of 30 minutes. The results showed homogeneity of groups (p> 0.05). There was an increase of SW in the GPBWS (p= 0.006) and GS in the GAS (p= 0.048) and decreased PDQ-39 in the CG (p= 0.005) and GAS (p= 0.006). For groups, regardless of evaluation, there were differences in SWV between the GPBWS and GAS (p= 0.030); for evaluations, independently of groups, there were differences in GS (p= 0.048) and PDQ-39 (p= 0.002). It was concluded that, among the studied conditions, there was a significant improvement for the groups: AS in GS and QOL, CG in QOL and GPBWS did not improve. Thus, considering the clinical effect, treadmill training, independently of the stimuli, is clinically advantageous for gait improvements and QOL. The aim of this study was to analyse and compare the effects of gait training on a treadmill associated with partial body weight support (PBWS) or auditory stimulus (AS) and the kinematic variables of gait and quality of life (QOL) in patients with Parkinson's disease (PD). Twenty-one volunteers with PD participated and were divided into: group with PBWS (GPBWS) with AS (GAS), and control group (CG). Soil step length (SL), SL variability (SLV), step width (SW), SW variability (SWV), gait speed (GS), and QOL were evaluated by the Parkinson's Disease Questionnaire-39 (PDQ-39). The training was performed for six weeks, with three weekly sessions of 30 minutes. The results showed homogeneity of groups (p> 0.05). There was an increase of SW in the GPBWS (p= 0.006) and GS in the GAS (p= 0.048) and decreased PDQ-39 in the CG (p= 0.005) and GAS (p= 0.006). For groups, regardless of evaluation, there were differences in SWV between the GPBWS and GAS (p= 0.030); for evaluations, independently of groups, there were differences in GS (p= 0.048) and PDQ-39 (p= 0.002). It was concluded that, among the studied conditions, there was a significant improvement for the groups: AS in GS and QOL, CG in QOL and GPBWS did not improve. Thus, considering the clinical effect, treadmill training, independently of the stimuli, is clinically advantageous for gait improvements and QOL.